High Power efficiency in optical logic X-OR gate structure - Mutmainnah Mutmainnah; Yono Hadi Pramono (Jurnal ILMU DASAR, 2009)
A High Power Efficiency of Optical Waveguide for Logic X-OR gate has been investigated numerically by means of FD-BPM (Finite Difference Beam Propagation Method). The proposed structure is designed by using of three Y-branches. Two of Y-branches structure is parallel combined in the input section and the other one is located with the opposite direction of the output section. The whole guiding structure is called 2x3 channel which having two-input ports and three-output ports. One of the gap between three output arms in the cladding region is assumed to be a nonlinear materials which will produce the phase shifting between its output optical fields. The magnitude of phase shifting is depending on the nonlinearity of material and the optical input power. Y-branch leg angle is also a significant parameter to increase efficiency of optical power switch. The numerical schemes showed that the proposed structure is suitable for optical switching especially for logic X-OR gate.